(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The research topic is devoted to Islam inherent in the Kazakh people and its relationship with traditions. The goal is to identify the elements of Islam characteristic of the traditions of the Kazakh people. The main idea of scientific research is to discourage some people who, after independence, on their own initiative, receive religious education abroad and express opinions against customs and traditions. The article focuses on the fact that there is no need to nullify the foundations of national identification that have evolved over the centuries. The concepts of innovation (bid’a) and polytheism (shirk) in religion are explained. It is also said about the groundlessness of accepting purely religious peculiarities and the rejection of such traditions as: a beta ball, a greeting for a daughter-in-law, a blessing, and one cannot alienate one’s own culture. In conclusion: Islam strongly influenced the worldview and was able to merge with the customs and traditions of the Kazakh people. The practical purpose of this article is to show the role of Islam and the influence on traditions for young people and the local population in general. The explanation of the topic of the connection of religion and traditions relevant for today’s Kazakh society with the help of illustrative examples can be called the value of the article. Key words: nationality, tradition, custom, interrelation, Islam, religion, Kazakh.